Glial fibrillary acidic protein as a biomarker in neuromyelitis optica spectrum disorder: a current review - Schindler, Patrick; Aktas, Orhan; Ringelstein, Marius; Wildemann, Brigitte; Jarius, Sven; Paul, Friedemann; Ruprecht, Klemens (Expert review of clinical immunology, 2023)
Introduction Neuromyelitis optica spectrum disorder (NMOSD) is a relapsing, often debilitating neuroinflammatory disease, whose predominant clinical manifestations are longitudinally extensive transverse myelitis and optic neuritis. About 80% of the patients with an NMOSD phenotype have pathogenic autoantibodies against the astrocyte water channel aquaporin-4 (AQP4-IgG). While therapeutic options for NMOSD have greatly expanded in recent years, well-established biomarkers for prognosis or treatment response are still lacking. Glial fibrillary acidic protein (GFAP) is mainly expressed in astrocytes and can be detected in cerebrospinal fluid (CSF) and blood of patients with NMOSD.Areas covered Here, we comprehensively review the current knowledge on GFAP as a biomarker in NMOSD.Expert opinion In patients with AQP4-IgG+ NMOSD, GFAP levels are elevated in CSF and serum during acute attacks and correlate with disability, consistent with the pathophysiology of this antibody-mediated astrocytopathy. Serum GFAP levels tend to be higher in AQP4-IgG+ NMOSD than in its differential diagnoses, multiple sclerosis, and myelin oligodendrocyte antibody-associated disease. Importantly, serum GFAP levels in AQP4-IgG+ NMOSD during remission may be predictive of future disease activity. Serial serum GFAP measurements are emerging as a biomarker to monitor disease activity in AQP4-IgG+ NMOSD and could have the potential for application in clinical practice.